Consequences of cryospheric change for water resources and hazards in the Hindu Kush Himalaya - Nepal, Santosh; Steiner, J. F.; Allen, S.; Azam, M. F.; Bhuchar, S.; Biemans, H.; Dhakal, M.; Khanal, S.; Li, D.; Lutz, A.; Pradhananga, S.; Ritzema, R.; et al. (International Centre for Integrated Mountain Development, 2023)
Chapter 3 of the Water, ice, society, and ecosystems in the HKH (HI-WISE) assessment report investigates the state of knowledge about the quality and quantity of climatic drivers, water resources, and their implications for present and future hydrological regimes. It also looks at water-related hazards and notes the most significant impacts recorded.